BRCA1 promoter methylation in peripheral blood is associated with the risk of triple‐negative breast cancer. Issue 5 (29th September 2019) - Prajzendanc, Karolina; Domagała, Paweł; Hybiak, Jolanta; Ryś, Janusz; Huzarski, Tomasz; Szwiec, Marek; Tomiczek‐Szwiec, Joanna; Redelbach, Wojciech; Sejda, Aleksandra; Gronwald, Jacek; Kluz, Tomasz; Wiśniowski, Rafał; et al.
Abstract : Methylation of the promoter of the BRCA1 gene in DNA derived from peripheral blood cells is a possible risk factor for breast cancer. It is not clear if this association is restricted to certain types of breast cancer or is a general phenomenon. We evaluated BRCA1 methylation status in peripheral blood cells from 942 breast cancer patients and from 500 controls. We also assessed methylation status in 262 paraffin‐embedded breast cancer tissues. Methylation status was assessed using methylation‐sensitive high‐resolution melting and was categorized as positive or negative. BRCA1 methylation in peripheral blood cells was strongly associated with the risk of triple‐negative breast cancer (TNBC) (odds ratio [OR] 4.70; 95% confidence interval [CI]: 3.13–7.07; p  < 0.001), but not of estrogen‐receptor positive breast cancer (OR 0.80; 95% CI: 0.46–1.42; p = 0.46). Methylation was also overrepresented among patients with high‐grade cancers (OR 4.53; 95% CI: 2.91–7.05; p  < 0.001) and medullary cancers (OR 3.08; 95% CI: 1.38–6.88; p = 0.006). Moreover, we detected a significant concordance of BRCA1 promoter methylation in peripheral blood and paired tumor tissue ( p  < 0.001). We found that BRCA1 promoter methylation in peripheral blood cells is associated with approximately five times greater risk of TNBC. We propose that BRCA1 methylation in blood‐derived DNA could be a novel biomarker of increased breast cancer susceptibility, in particular for triple‐negative tumors. Abstract : What's new? BRCA1 / 2 gene mutations are known risk factors for breast cancer, but how DNA methylation of the BRCA gene promoters, especially in peripheral blood cells, is correlated with breast cancer risk is less clear. Here the authors find that BRCA1 promoter methylation in blood‐derived DNA is associated with ~5‐fold increased risk for triple‐negative breast cancer, underscoring its relevance as a biomarker for this treatment‐resistant form of breast cancer.